Strategi Guru Mengatasi Perilaku Disruptif Siswa dalam Mendukung Pembelajaran Efektif - Rika Nopiyanti; Nunung Nur'aeni; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
Student disruptive behavior is one of the problems faced by many elementary school teachers in managing classes, especially for lower grade students who are in the transition period from play to formal learning so that they do not yet have fully mature self-control. This study aims to describe and analyze teacher strategies in dealing with student disruptive behavior to support effective learning. This study uses a case study approach. Data were collected through participant observation, semi-structured interviews, and documentation studies. Data analysis was carried out using the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions, with data validity guaranteed through triangulation of sources, techniques, and time. The results of the study indicate that (1) The most dominant disruptive behavior is talking outside the learning context, followed by behavior that disturbs friends, walking around without permission, and not paying attention to teacher explanations; (2) Supporting factors for the implementation of teacher strategies include pedagogical competence, teaching experience, school environmental support, and parental support, while inhibiting factors include less varied teaching methods, limited facilities and equipment, lack of parental attention, peer influence, and teacher emotional exhaustion. This study concludes that appropriate and correct teacher strategies can overcome disruptive behavior and make a positive contribution to effective learning.